Hubungan Antara Keterampilan Berpikir Kritis Dan Prestasi Akademik Mahasiswa - Rosania Waruwu; Yogiarno Waruwu (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2024)
This study aims to analyze the relationship between critical thinking skills and students' academic achievement. Critical thinking skills are considered important in the learning process, because they allow students to analyze information, evaluate arguments, and make the right decisions. The research method used is quantitative with a correlational approach. The research sample consisted of 150 students from various study programs at a university. Data were collected through questionnaires to measure critical thinking skills and academic documents for academic achievement. The results of the analysis showed that there was a significant positive relationship between critical thinking skills and academic achievement, where students with higher critical thinking skills tend to have better academic achievement. This finding indicates the need for the development of critical thinking skills in the higher education curriculum to improve students' academic achievement.